Yungahelea, a new genus of predaceous midge from northwestern Argentina (Culicomorpha: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2018)
A new monotypic genus and species of predaceous midge from the southernmost area of the Argentinean Yungas, Yungahelea australis Spinelli and Ronderos, is described and illustrated from male and female adults. It belongs to a group containing the Ceratopogonini genera Parabezzia Malloch, Diaphanobezzia Ingram and Macfie, Spinellihelea Borkent, Grogan and Picado, Leptohelea Wirth and Blanton, and Fittkauhelea Wirth and Blanton. Phylogenetic interpretation indicates that Yungahelea is the sister group of Spinellihelea or the clade composed by Parabezzia and Diaphanobezzia.